2021
DOI: 10.1177/01454455211002105
|View full text |Cite
|
Sign up to set email alerts
|

Thwarted Belongingness and PTSD Symptom Severity among Firefighters: The Role of Emotion Regulation Difficulties

Abstract: The present investigation examined the associations among thwarted belongingness (TB), emotion regulation difficulties (ERD), and posttraumatic stress disorder (PTSD) symptom severity among firefighters. First, the associations of TB and ERD with PTSD symptom severity were evaluated. Second, the indirect effect of TB on PTSD symptom severity through ERD was examined. The sample included 246 trauma-exposed firefighters ( M age = 40.21, SD = 9.93, 93.1% male) who completed an online questionnaire battery. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Leonard and Vujanovic (2021) examined the relationship between thwarted belongingness, emotion regulation difficulties, and PTSD symptom severity in trauma-exposed firefighters. Their results showed that perceived or actual social disconnectedness in this sample was related to greater emotion regulation difficulties and greater levels of PTSD symptoms.…”
mentioning
confidence: 99%
“…Leonard and Vujanovic (2021) examined the relationship between thwarted belongingness, emotion regulation difficulties, and PTSD symptom severity in trauma-exposed firefighters. Their results showed that perceived or actual social disconnectedness in this sample was related to greater emotion regulation difficulties and greater levels of PTSD symptoms.…”
mentioning
confidence: 99%
“…This study was a secondary analysis of data from a larger project examining stress and health-related behaviors among firefighters (Leonard & Vujanovic, 2022). The current sample included 155 firefighters (93.5% male; M age = 42.2, SD = 9.8) recruited online from career, volunteer, and combination (i.e., volunteer and career) departments in and around a large metropolitan area in the southern United States.…”
Section: Participantsmentioning
confidence: 99%
“…Firefighter PTSD symptom severity has been associated with various factors. Some of these factors include thwarted belongingness, anxiety sensitivity, emotional regulation difficulties, high levels of self-blame, low levels of social support, negative emotionality, and negative self-appraisal (Bryant & Guthrie, 2007; Lebeaut et al, 2022; Leonard & Vujanovic, 2022; Meyer et al, 2012, 2021; Paltell et al, 2019). Interestingly, firefighters appear to have low rates of PTSD and depression over the first 3 years of their career despite experiencing numerous traumatic incidents (Gulliver et al, 2021).…”
mentioning
confidence: 99%